Análisis de participación ciudadana del “Noticiero de la comunidad” de TVS en la audiencia de adultos entre 40 a 50 años de la ciudad de Riobamba, periodo octubre - diciembre de 2023. - Iguasnia Amaguaya, Erika Mishel (2025)
This research examines the programming of the community news broadcast on TVS Channel 13 in the city of Riobamba, with the objective of evaluating how adults aged 40 to 50 engage in civic participation through the content of the community news program during the period of October to December 2023. The purpose is to analyze the programming content and investigate how information is handled and prepared for broadcast. Additionally, the study aims to identify the types of news stories that generate the greatest impact and acceptance among citizens. A total of 10 news reports were analyzed between October and December 2023. For this analysis, an observation matrix was developed to collect accurate data from the selected news items. The research reveals that the programming content meets the basic conceptual requirements for news production. It was also found that the content is generated through a daily agenda that selects the most relevant topics, which contributes to the dissemination of objective information and the diversity of news coverage